The Knowledge as a Service Metaphor and its Use for Building Convergence Environments - Amaro, Manoel; Lino, Natasha Queiroz; Siebra, Clauirton; Guedes, Alan (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The Interactive TV (ITV) advances are enabling the development of modern applications in this platform. However, several of such applications could take advantages from a convergence environment, where they could access information and services from other platforms. The Web servers, in particular the knowledge servers, present interesting properties to the configuration of a convergence environment. This work explores such properties as a way to support convergence between the Web and ITV platforms.